ANALISIS YURIDIS TERHADAP PENERAPAN SISTEM SHOP PADA TIKTOK: Juridical Analysis Of The Implementation Of The Shop System At Tiktok - Diouf Dihyan Gantari Munif; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2024)
Based on Law No. 11 of 2008 concerning ITE, social commerce, which is a combination of social media and e-commerce, is prohibited from facilitating payment transactions on electronic systems. This prohibition applies to platforms such as TikTok and Tokopedia. This study aims to examine the formulation of the problem regarding the implementation of the Shop system on TikTok as social media and Tokopedia as e-commerce according to legal regulations in Indonesia, as well as the obstacles that arise. Using normative legal methods and descriptive approaches, secondary data are analyzed qualitatively and concluded with deductive logic. The results of the research and discussion show that the TikTok Shop system violates Article 21 paragraph (3) of Permendag 31 of 2023 concerning Electronic System Organizers for Trade (PPMSE), because it continues to facilitate payment transactions through its electronic system, which should be prohibited according to applicable regulations